Sport-specific repeated sprint training improves punching ability and upper-body aerobic power in experienced amateur boxers - Kamandulis, S.; Bruzas, V.; Mockus, P.; Stasiulis, A.; Snieckus, A.; Venckunas, T. (The Journal of Strength and Conditioning Research, 2018)
High-intensity interval training improves endurance and performance, but it is unclear whether sprint-type upper-body interval training is similarly effective. This study explored the effects of 4-week sport-specific sprint interval training on punch characteristics and endurance capacity in boxers. Experienced male amateur boxers (n = 18) participated in this 4-week training study and were divided into an experimental group (EG) and a control group (CG) (n = 9 per group). Both groups completed standard low-intensity training. The EG also completed 3 rounds (14 sets of 3-second all-out punching with a 10-second rest) of a simulated fight using a punching bag with a 1-minute rest between rounds 3 times per week, whereas the CG performed the same 3 rounds of a simulated fight at low intensity. Three rounds of 14 sets of 3-second all-out punching of a bag ergometer with a 10-second rest were performed to measure punching abilities. Peak oxygen consumption and peak power were measured during progressive arm cranking before and after training. In response to training peak oxygen consumption and peak power in arm-cranking test increased in EG, also punching force increased and maintenance of punching frequency and punch force improved during the simulated fight, which resulted in greater cumulative force throughout the 3 rounds. There were no changes in the CG. The study shows that 1 month of all-out punching training (3 sessions per week with ~2 minutes of all-out punching per session) improved both upper-body aerobic power and punching abilities in experienced amateur boxers.